Floor Disturbance and Failure Characteristics of Super-Large Mining Height Working Face - Cunjin Lu; Jinpeng Xu; Hui Zhao; Heng Zhang; Yian Zhang; Mingyue Chen (Geofluids)
The failure depth of the working face floor caused by mining is a key parameter to predict water inrush from the working face floor. Extensive research has been conducted on the floor failure zone of the working face. However, in recent years, there have been few studies on the floor failure law of the working face with a super-large mining height (over 20 m) in the western mining area of China. In this paper, the working face with a super-large mining height of 24 m in Longwanggou Coal Mine was studied. Electrical monitoring and numerical simulation of the working face floor were carried out. The measured floor failure depth of the working face is 15 m while the average numerical simulation result is 11 m. When compared with the calculation results of the statistical analysis formulas, the floor failure depth of the working face with a super large mining height obtained from field measurement and numerical simulation is smaller. The reason for the smaller failure zone of the floor of the super large mining height working face is that the falling roof inhibits the pressure relief of the floor, the large mining height reduces the advance pressure, and the shear stress of the floor decreases. The research methods and findings are of great significance to the prediction of floor failure and water inrush in working face with a super-large mining height, the prevention and control of water disasters in coal seam roof and the monitoring of mine pressure.